An Uncommon Incidence of Pulmonary Hypertension Associated With Neurofibromatosis Type 1: A Case Report. (July 2021) - Rao, Suman; Khan, Alisha; Sampat, Parth; Sandhu, Michael; Weinberg, Andrew M.
Pulmonary hypertension (PH) is often a difficult condition to diagnose, since it occurs insidiously and is a diagnosis of exclusion. Patients with neurofibromatosis type 1 (NFT1) have been associated with severe exacerbations of PH. To our knowledge, less than 20 cases of PH in NFT1 patients have been reported. However, the severity of presenting symptoms requires physicians to be aware of this association and pursue the appropriate diagnostic workup. In our report, we present a 54-year-old NFT1 patient who presented with worsening dyspnea secondary to PH, which was being treated with trepostanil and macitetan. She required a right heart catheterization to assess her pulmonary artery pressures (which remained elevated). She was placed on tadalafil in addition to trepostanil and macitetan and noted significant resolution of her symptoms. Further studies are required to explore the association between PH and NFT1 and examine the efficacy of triple therapy with endothelin receptor antagonists, phosphodiesterase 5 inhibitors, and parenteral prostanoids in the initial treatment of PH in the aforementioned patient population.